Waterland - Swift, Graham, 1949- (Vintage Books, 1992)
Set in the bleak Fen Country of East Anglia, and spanning some 240 years in the lives of its haunted narrator and his ancestors, Waterland is a book that takes in eels and incest, ale-making and madness, the heartless sweep of history and a family romance as tormented as any in Greek tragedy. "" Waterland , like the Hardy novels, carries with all else a profound knowledge of a people, a place, and their interweaving ... Swift tells his tale with wonderful contemporary verve and verbal felicity ... A fine and original work.""-- Los Angeles Times.